AC breakdown voltage performance of refined, bleached and deodorized palm oil and mineral oil in the presence of multiple contaminations - Shukri, Muhammad Safwan (2021)
Refined Bleach and Deodorized Palm Oil (RBDPO) is one of the alternatives considered for Mineral Oil (MO) for possible application in transformers. It is biodegradable, environmentally friendly and non-toxic. In addition, the electrical performances of dried and filtered RBDPO is comparable with MO. Currently, there is only few studies that have been carried out to examine the effect of individual contaminants i.e. moisture, copper and cellulose particles on the AC breakdown voltage of RBDPO under separate experimental works. Systematic comparison of the individual contaminants under the same experimental setup is quite important to obtain overall overview of the effects on the AC breakdown voltage of RBDPO. Furthermore, there is no study that has been carried out to examine the combined contaminants impact on the AC breakdown voltage of either MO and RBDPO. This study aims to examine the effect of individual and combined contaminants i.e. moisture, copper and cellulose particles on the AC breakdown voltages of RBDPO. MO was also examined on this study for comparison purpose. The first study examined the effect individual contaminant on the AC breakdown voltage of RBDPO and MO. The particles to oils weight ratios were set to various weight. Next, the AC breakdown voltage of RBDPO and MO were investigated in the presence of combined contaminants. The total particles to oils weight ratios were set at various weight and at different levels of moisture. Finally, statistical analyses utilizing normal, Weibull and lognormal distribution functions were carried out to evaluate the AC breakdown voltage performances of RBDPO and MO under the influence of either individual and combined contaminants. It is found that moisture has significant impact on the AC breakdown voltage of RBDPO and MO. The AC breakdown voltage of RBDPO experiences significant reduction at higher level of moisture as compared to MO. Under low moisture content, the sudden reductions on AC breakdown voltage patterns for both RBDPO and MO in the presence of copper particles are quite similar. Meanwhile, the AC breakdown voltage reduction of RBDPO occurs at higher number of cellulose particles as compared to MO. On the contrary, the increment of number of cellulose particles could lead to the AC breakdown voltage increments of RBDPO and MO at medium and high moisture levels. The presence of higher weight ratio of copper is more dominant as compared to cellulose particles on the reduction of AC breakdown voltages for both RBDPO and MO. Based on the Anderson-Darling test, Weibull distribution has been found to be the suitable to represent most of the data on this study. Hence, the prediction on the AC breakdown voltages for RBDPO and MO has been developed. The estimated AC breakdown voltage based on Weibull equation is mostly has percentage difference of less than 5% as compare to the measured AC breakdown voltage for RBDPO and MO whereby the highest percentage difference is 20.83%.